The economic value of realized volatility: Using high-frequency returns for option valuation - Peter Christoffersen; Bruno Feunou; Kris Jacobs; Nour Meddahi (Bank of Canada, 2012)
Many studies have documented that daily realized volatility estimates based on intraday returns provide volatility forecasts that are superior to forecasts constructed from daily returns only. We investigate whether these forecasting improvements translate into economic value added. To do so we develop a new class of affine discrete-time option valuation models that use daily returns as well as realized volatility. We derive convenient closed-form option valuation formulas and we assess the option valuation properties using S&P500 return and option data. We find that realized volatility reduces the pricing errors of the benchmark model significantly across moneyness, maturity and volatility levels.
Keywords: G13; 330; Asset pricing; Econometric and statistical methods